CLOUD SERVICES AS A MEANS OF GAMIFICATION IN THE TRAINING OF FUTURE TEACHERS - Titova, Liubov; Kryvoruchko, Inna (Journal of Information Technologies in Education (ITE), 2024)
The relevance of using cloud services as one of the means of gamification of the educational process is becoming increasingly evident in the context of modern challenges of higher education. The article analyzes the experience of domestic scientists in the implementation of gamification technology in the educational process of higher education institutions. The researchers focus on both game simulators as an effective means of gamification and the capabilities of cloud services, in particular Kahoot!, LearningApps and Wordwall. The article also examines such cloud services as Kahoot!, LearningApps, Wordwall, Educaplay, Classtime, explores their main functionalities and considers which elements of gamification technology (game rules, leaderboards, points, game aesthetics, etc.) are included in these environments and how they affect the learning process of higher education students. A comparative characterization of the mentioned services is made according to the following features: functionality, type of content, gamification elements, visualization, integration with other platforms, interface languages, free and paid tariffs. The article also highlights the results of a survey of first-year students of the Faculty of Physics, Mathematics and Informatics of Pavlo Tychyna Uman State Pedagogical University, specialties «Secondary Education (Mathematics. Computer Science)» and «Secondary Education (Computer Science)» of the 2022/2023 and 2023/2024 academic years, on their familiarity with the concept of «gamification technology», as well as on determining the most effective and convenient, in their opinion, gamified cloud tool. As a result of the survey, the majority of respondents chose LearningApps for its extensive and free tools, and Kahoot! for its interactive and visually appealing service. In addition, both services are well known to students from school, which played a key role in their choice. The study concluded that cloud services are a widely used tool in educational activities, they make it possible to make the educational process interactive and interesting, while gamification elements often serve as a motivating factor and allow students to fully immerse themselves in the game-based learning environment. This approach contributes to better assimilation and understanding of educational material, as well as to improving the efficiency and quality of the educational process.